The Role of Psychological Capital on Employee Voice: Conservation Resources Framework - unika prihatsanti; Seger Handoyo; Rahkman Ardi; Puji Tania Meliala (Universitas Ahmad Dahlan, 2020)
The current study aims to explain how psychological capital influences employee voice in the Indonesian context. The conservation resources framework can provide an explanation of how personal resources, namely psychological capital (psycap) have an impact on work behavior (employee voice). This study involved 182 participants from various companies. Questionnaires were circulated via an instant messaging application, several social media platforms, and paper-based. Based on a simple regression analysis, it is proven that psychological capital is significantly related to employee voice. Employees can choose to speak up when they are motivated by a pro-social motive that brings to constructive changes to themselves and the organizations. Psycap interacting simultaneously produces different manifestations, which can make individuals obtain new resources. By acquiring these additional resources, individuals are ready to meet the demands of work and achieve their work goals, by providing a voice.